Synthesis and Spectral Studies of Manganese(II), Cobalt(II), Nickel(II), Copper(II), Chromium(III) and Iron(III) Complexes of Schiff Base Derived from Hydrazine hydrate - Kushwaha, B.S.; Kumar Rathore, Deep (Asian Journal of Chemistry, 2010)
The Schiff base p-methoxy phenyl carbonyl hydrazone (PMPCH) and its complexes with Mn(II), Co(II), Ni(II) Cu(II), Cr(III) and Fe(III) have been prepared and characterized on the basis of analytical, magnetic measurements, IR and electronic spectral data. Various ligand fields and different parameters have been found to be consistent with octahedral structure. Schiff bases and some complexes have been tested against the fungi A. niger and A. flavus.